Analysis of Water Quality in Sea Waters After The Sea Snot Occurrence in Bima Bay West Nusa Tenggara - S. Kasim; N. A. Pratiwi; H. Natsir; S. Liong; I W. Sutapa (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2025)
The incident that occurred in April 2022 in Bima Bay was a phenomenon that shocked the residents of Bima City and outside the Bima area. Based on previous laboratory tests, the cause is Sea Snot which is accompanied by an explosion in the number and metabolism of algae. The entry of organic and inorganic pollutants into water bodies can cause water quality to experience degradation in biological function. This research aims to analyze water quality in marine waters with the parameters BOD, COD, DO, determine the Nitrate and Phosphate content and characterize total coliform and E. coli bacteria in marine waters. This research uses electrometric, photometric and membrane filtrate methods. pH ranged from 7.85 - 8.22; DO levels 5.97 - 6.15 mg / L, BOD 1.3, and 5 ranged from 5.52 - 9.06 mg / L. COD levels 15.62 - 21.44 mg / L. Nitrate ranges from 0.124 - 0.204 mg/L. Phosphate ranges from 0.27 - 0.41. Total coliform bacteria ranges from 706 - 1,266 colonies/100 mL and E. coli 0.75 - 1.75 colonies/100 mL. The water quality in the sea waters of Bima Bay has mostly met the sea water quality standards for the parameters BOD, DO, total coliform, E. coli , while the COD parameter is not included in the mandatory parameters which are one of the indicators of sea water pollution. The content of Nitrate and Phosphate in the waters of Bima Bay shows that its value has exceeded the sea water quality standards.